Towards the total synthesis of apicularen A - Chan, Jocelyn Li Ting (2010)
This thesis involves the synthesis of an intermediate towards Apicularen A utilizing indium-mediated conjugate addition of a thioester derived ketene to a conjugated ketone. This yields the important trans-2,6-hydroxypyran ring essential for its bioactivity as a potential anti-cancer agent.